Bulk‐Heterojunction Organic Solar Cells: Five Core Technologies for Their Commercialization. Issue 36 (27th June 2016) - Kang, Hongkyu; Kim, Geunjin; Kim, Junghwan; Kwon, Sooncheol; Kim, Heejoo; Lee, Kwanghee
Abstract : The past two decades of vigorous interdisciplinary approaches has seen tremendous breakthroughs in both scientific and technological developments of bulk‐heterojunction organic solar cells (OSCs) based on nanocomposites of π‐conjugated organic semiconductors. Because of their unique functionalities, the OSC field is expected to enable innovative photovoltaic applications that can be difficult to achieve using traditional inorganic solar cells: OSCs are printable, portable, wearable, disposable, biocompatible, and attachable to curved surfaces. The ultimate objective of this field is to develop cost‐effective, stable, and high‐performance photovoltaic modules fabricated on large‐area flexible plastic substrates via high‐volume/throughput roll‐to‐roll printing processing and thus achieve the practical implementation of OSCs. Recently, intensive research efforts into the development of organic materials, processing techniques, interface engineering, and device architectures have led to a remarkable improvement in power conversion efficiencies, exceeding 11%, which has finally brought OSCs close to commercialization. Current research interests are expanding from academic to industrial viewpoints to improve device stability and compatibility with large‐scale printing processes, which must be addressed to realize viable applications. Here, both academic and industrial issues are reviewed by highlighting historically monumental research results and recent state‐of‐the‐art progress in OSCs. Moreover, perspectives on five core technologies that affect the realization of the practical use of OSCs are presented, including device efficiency, device stability, flexible and transparent electrodes, module designs, and printing techniques. Abstract : Bulk‐heterojunction organic solar cells based on solution‐processable organic semiconductors enable completely new functionalities of being printable, portable, wearable, biocompatible, and attachable to any curved surfaces. The recent major advances in device efficiency and stability, flexible transparent electrodes, module design, and printing technologies for their commercialization are reviewed. The existing challenges and perspectives for these five core technologies are discussed.